1995
DOI: 10.1172/jci117843
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Gs alpha protein in the hearts of transgenic mice.

Abstract: Alterations in fi-adrenergic receptor-G.-adenylyl cyclase coupling underlie the reduced catecholamine responsiveness that is a hallmark of human and animal models of heart failure. To study the effect of altered expression of Gs., we overexpressed the short isoform of Gs,, in the hearts of transgenic mice, using a rat a-myosin heavy chain promoter. G.. mRNA levels were increased selectively in the hearts of transgenic mice, with a level 38 times the control. Despite this marked increase in mRNA, Western blotti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
73
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(79 citation statements)
references
References 30 publications
5
73
1
Order By: Relevance
“…However, previous studies in the heart have shown that ␤AR overexpression does not yield a proportional increase in agonist-promoted stimulation of cAMP production (3,4). Similarly, overexpression of cardiac G␣s has limited effects on adrenergic responsiveness (5). In contrast, the present study indicates that overexpression of AC VI in cardiac myocytes is associated with a robust amplification of ␤AR-mediated signaling.…”
Section: Resultscontrasting
confidence: 75%
See 2 more Smart Citations
“…However, previous studies in the heart have shown that ␤AR overexpression does not yield a proportional increase in agonist-promoted stimulation of cAMP production (3,4). Similarly, overexpression of cardiac G␣s has limited effects on adrenergic responsiveness (5). In contrast, the present study indicates that overexpression of AC VI in cardiac myocytes is associated with a robust amplification of ␤AR-mediated signaling.…”
Section: Resultscontrasting
confidence: 75%
“…Variations in cell preparation, viral titer, and cAMP assays may contribute to the range in cAMP production that we found. Previous studies examining augmentation of transmembrane adrenergic signaling by altering ␤AR or Gs expression (3)(4)(5) or inhibiting G-protein coupled receptor kinase function (12) typically achieve no more than a 2-fold increase in cAMP production.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that adenylyl cyclase is the critical component that limits maximal response to the ␤-adrenergic receptor (22). Thus, overexpression of the receptor (or G s ) in isolated cells (23) or transgenic animals (24) results in only modest enhancements in activation. We thus titrated the plasmid DNA used for our transfection (0.025-2.0 g of DNA/ ml) using equal concentrations for hIP1D4 and R212H (Fig.…”
Section: Fig 2 Competition Binding For Hip1d4pmt4 V25m and R212hmentioning
confidence: 99%
“…19 We attempted to achieve cardiac specific gene expression by cloning the rat ␣-myosin heavy chain promoter (␣MyHC) in a recombinant adenovirus. To maximize cloning capacity, we have employed a short version of the ␣MyHC promoter (Ϫ613 to +32) that is sufficient for directing high levels of cardiac-specific gene expression in transgenic mice, 20,21 as well as after direct gene injection. 22 However, when a recombinant adenovirus carrying the ␣MyHC promoter driving the chloramphenicol report gene (CAT) was tested in vivo by direct injection, we found that CAT expression was not restricted to the heart, but was also detectable in several tissues (data not shown).…”
mentioning
confidence: 99%